Saints, statues, and stories : a folklorist looks at the religious art of Sonora - Griffith, James S. (Southwest Center series., 2019)
"This book considers the history and aesthetics of religious artwork in official and traditional Catholic contexts, examining the role that this religious art plays in the northwestern state of Sonora, Mexico"--